2016
DOI: 10.4103/0019-5545.174355
|View full text |Cite
|
Sign up to set email alerts
|

Stigma of tiger attack: Study of tiger-widows from Sundarban Delta, IndiaFNx01

Abstract: Aims:Human-tiger conflict (HTC) is a serious public health issue in Sundarban Reserve Forest, India. HTC is a continued concern for significant mortality and morbidity of both human and tiger population. This study examined 49 widows, whose husbands were killed by tigers, in order to explore the cultural stigma related with tiger-killing and consequent discrimination and social rejection. Different psychosocial aspects of community stigma associated with tiger-killings is discussed in the context of local cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Similarly, islanders in the Sundarban Delta strongly believe that worshiping Bonobibi, the forest's guardian goddess, and Dakkhin Ray, the tiger God, before entering forests for fishing and collecting honey and fire woods, would protect them from dangers and misfortune, such as negative climatic events and animal attacks. Consequently, the islanders perceive the forest as an "ecomother" which is a result of a complex interplay between ecology, culture, and spirituality (Chowdhury et al 2016). Concurrently, we acknowledge that culture does not exist in a vacuum outside state apparatuses and therefore research on adaptation pathways needs to continue to pay attention to power relations within the state and between the state, its intermediate agencies, and other actors (Nightingale et al 2020).…”
Section: Cultural Beliefs and Valuesmentioning
confidence: 96%
“…Similarly, islanders in the Sundarban Delta strongly believe that worshiping Bonobibi, the forest's guardian goddess, and Dakkhin Ray, the tiger God, before entering forests for fishing and collecting honey and fire woods, would protect them from dangers and misfortune, such as negative climatic events and animal attacks. Consequently, the islanders perceive the forest as an "ecomother" which is a result of a complex interplay between ecology, culture, and spirituality (Chowdhury et al 2016). Concurrently, we acknowledge that culture does not exist in a vacuum outside state apparatuses and therefore research on adaptation pathways needs to continue to pay attention to power relations within the state and between the state, its intermediate agencies, and other actors (Nightingale et al 2020).…”
Section: Cultural Beliefs and Valuesmentioning
confidence: 96%
“…Stigma and discrimination related with Tiger attack: Chowdhury et al [56] in their study by using a measurement of stigma showed that the Tiger-widows are more stigmatized than both normal and snake-bite widows. It is interesting to note that in cases of tiger-widows (in contrast to other widows), a social belief and superstition relating to tiger attack/killing is operative as a strong determinant of stigma.…”
Section: Cultural Risk: Cultural Belief About Forest-dependence Onmentioning
confidence: 99%
“…Those who are widowed owing to the death of their husbands are more likely to experience severe stress than those who are divorced (Gayatri 2016). Widows are vulnerable to social sanctions in the form of discrimination, fear, negative feelings, trauma, abuse, and exploitation (Chowdhury et al 2016). Widows require social support in the form of friendship in the social environment in order to avoid feeling isolated and discriminated against (Huisman & Lemke 2020).…”
Section: Introductionmentioning
confidence: 99%